Filozoficzne i metodologiczne podstawy historii komunikacji - Wendland, Michał (Wydawnictwo Naukowe UAM, 2015)
It was not long ago that the contemporary humanities started to deal with communication-related phenomena, and yet these phenomena are among those areas of the science of communication, which is also called communicology, that are developing most rapidly. This book explores the history of communication which is understood as a subdiscipline of communicology, i.e. a field of science that focuses on past communication practices, past means and forms of communication (the media) as well as collective notions of communication of the past. The monograph is mainly methodological and philosophical in nature, and it deals with history to a much lesser extent. This means that it does not provide a cross-sectional perspective on the history of human communication or a systematic overview of historical- philosophical stances on communication. The methodological foundations of the history of communication are the main topic of this book, which attempts to answer the question of how this field of knowledge can be studied. The book presents the most important methodological guidelines which are formulated with reference to the history of communication, and mainly to a culturalist approach. Probably the most significant assumption made in this book is that communication constitutes one of the areas of symbolic culture and that communication and culture are inextricably bound with each other. Consequently, as regards methodology, the book concludes and postulates that the study of past communication is closely related to such fields of the humanities as the history of culture (cultural history) and anthropology of culture, and it is not only limited to exploring the forms and means of communication, i.e. the media, of the past.
Keywords: communication; history